2021
DOI: 10.1101/2021.01.27.21250517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection and transmission in school settings during the second wave in Berlin, Germany: a cross-sectional study

Abstract: BackgroundSchool attendance during the SARS-CoV-2 pandemic is intensely debated. Modelling studies suggest that school closures contribute to community transmission reduction. However, data among school-attending students and staff are scarce. In November 2020, we examined SARS-CoV-2 infections and seroreactivity in 24 randomly selected school classes and connected households in Berlin, Germany.MethodsStudents and school staff were examined, oro-nasopharyngeal swabs and blood samples collected, and SARS-CoV-2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
(30 reference statements)
1
20
0
Order By: Relevance
“…In another study at peak transmission in Berlin, early November 2020, 1.4% of 140 teachers were found to be infected [4], confirming our findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In another study at peak transmission in Berlin, early November 2020, 1.4% of 140 teachers were found to be infected [4], confirming our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Such concerns, in turn, impact on the functionality of schooling and childcare [1]. While the influence of opened or closed educational facilities on the course of the pandemic has been subject to modelling [2] and observational studies [3][4], with partially contradicting findings, the actual occupational risk of educational staff is less clear. Repeatedly changing infection prevention and control (IPC) measures, such as to mask wearing obligations or divided classes, also make it difficult to draw firm conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent empirical work from multiple countries that correlates school re-opening to local Rt direction changes and secondary infection clusters increasingly confirms earlier findings of minimal contribution of educational settings to the community COVID-19 growth rates [36][37][38][52][53][54]: open schools of all grades may be considered safe and will not act as amplifiers of Sars-CoV-2 spread at times of low COVID-19 background prevalence. In fact, it appears that adults, and not children, play a key role in bringing the virus into their households [39,55], and that in-school COVID-19 incidence is directly consequential to local background prevalence [40,41,56,57].…”
Section: Introductionmentioning
confidence: 55%
“…Furthermore, as synthesized in a large systematic review [47], multiple organizational, environmental and surveillance measures have been implemented heterogeneously worldwide to minimize the risk of in-class infection, including highly effective test-and-trace strategies, decreased class size, opening for specific cohorts in a staggered timetable, lessons held outdoors, physical distancing as well as hygiene measures in the classroom, the creation of social bubbles limiting contacts between those who rarely meet, and the instruction to stay at home when sick [48][49][50]. Although successfully curtailed school-related outbreaks are less likely to be reported in the literature than outbreaks that have occurred, we have sufficient real-world evidence indicating that different types of infection control measures may effectively either avert or minimalize COVID-19 clusters among students [51][52][53][54]. While the efficacy of each measure has been extensively modelled, very few experimental and quasi-experimental studies have been published assessing the effectiveness of specific measures, including one finding that lower physical distancing policies may safely be adopted in school settings [55].…”
Section: Introductionmentioning
confidence: 96%
“…11 Longitudinal seroprevalence studies conducted in schools are beginning to advance our knowledge of school-based SARS-CoV-2 transmission among children, staff and families. [14][15][16] For example, studies conducted in French 17 and British 16 primary schools suggested little evidence of transmission from children to their peers or teachers, while a large Swiss cohort 18 found minimal clustering of seropositive cases within classes and schools despite a clear increase in seroprevalence in children over a 5-month period of very high transmission.…”
Section: Introductionmentioning
confidence: 99%